Ideal government and the mixed constitution in the Middle Ages - Blythe, James M. 1948- (Princeton University Press, 1992)
Cover -- Contents -- Part 1: The Mixed Constitution -- Part 2: Thomas Aquinas and His Successors -- Part 3: The Fourteenth Century -- Part 4: The Fifteenth Century and the Early Modem Period